Post-Exercise Passive Heat Exposure in Athletes - A Systematic Review of Recovery, Performance, and Adaptation - Burda, Dawid; Galas, Karolina; Adamczyk, Oliwier; Cebula, Wiktoria; Orankiewicz, Julita; Dusińska, Dominika; Błażej, Bartłomiej; Płomińska, Zuzanna; Akonom, Piotr; Grabowska, Julia (Quality in Sport, 2026)
Background. Post-exercise passive heat exposure, including sauna bathing, infrared sauna, and hot-water immersion, has been proposed as a strategy to influence recovery, performance, and adaptation in sport, but the evidence remains heterogeneous. Purpose. To assess the effects of post-exercise passive heat exposure on recovery-, performance-, and adaptation-related outcomes in athletes and trained individuals. Methods. PubMed and Scopus were searched on 18 March 2026 and supplemented by citation tracking and manual reference screening. Eligible studies examined passive whole-body heat exposure after exercise, training, or competition. Linked reports were grouped. Findings were synthesized narratively, and a retrospective risk-of-bias assessment was performed. Results. Thirteen study programs were included. The most favorable pattern was observed in repeated endurance-oriented applications, particularly when passive heat appeared to support heat adaptation. Acute effects were mixed and outcome-specific, whereas evidence in team-sport, strength-, power-, and hypertrophy-related settings was limited and mostly neutral. Conclusion. Post-exercise passive heat exposure appears to have selective rather than general effects in athletes. Current evidence does not support broad claims of consistent benefit across athletic settings.